KM implementation in Malaysian telecommunication industry: An empirical analysis - Chong, Chin Wei; Chong, Siong; Heng, Paul Ping Yeow (Emerald Publishing Limited, 2006)
Purpose - This paper aims assess to the perceived importance (PI) and actual implementation (AI) of five preliminary knowledge management (KM) success factors, i.e. business strategy, organizational structure, knowledge team, knowledge audit, and knowledge map in the Malaysian telecommunication industry.